General Procedures in Single-Case Research - Barker, Jamie; McCarthy, Paul; Jones, Marc; Moran, Aidan (Single-Case Research Methods in Sport and Exercise Psychology, 2011)
In this chapter, we will outline issues to consider in: the planning of single-case research; the conduct of single case-research; the interpretation of data in single-case research.